Beyond the known: Unraveling the existence of novel Trichinella genotypes (T14 and T15) in India and expanding the species complex - Rasmita Panda; Anil Kumar Nehra; Hira Ram; Mathesh Karikalan; Priyanka Kumari; Rajat Garg; Partha Sarathi Banerjee; Abhijit Pawde; Aditi Sharma; Mukesh Gupta; Raj Kumar Singh (Journal of Genetic Engineering and Biotechnology)
The Trichinella species complex includes 10 recognized species and three genotypes with global distribution, impacting significant health and economic burdens on livestock, wildlife, and humans. In India, trichinellosis is an under recognized zoonotic disease. Investigating the taxonomic status, genetic diversity and phylogeography of Indian Trichinella isolates is crucial for understanding the disease's regional dynamics. This study used International Commission on Trichinellosis (ICT) recommended multiplex PCR (mPCR) followed by sequencing for identification of the Indian Trichinella isolates up to species level. Multiplex PCR assay yielded band pattern similar to either single infection with T. nelsoni or mixed with T. britovi in leopards and tigers. However, sequencing of mPCR products revealed an increase in base composition. Further molecular characterization was performed using five nuclear genes/regions (18S rRNA, 5S ISR, ESV, ITS1, and ITS2), and three mitochondrial genes (coxI, cytb, and mt-lsr). Phylogenetic analyses (maximum likelihood and Bayesian inference) based on the molecular markers (coxI, 5S ISR, ITS1, and ITS2) highlighted the genetic variation among the Indian isolates, and positioned them as sister clades to T. britovi or T. nelsoni or as an independent taxon. Furthermore, the variable region of ESV also presented a series of unique nucleotides in the Indian isolates which unequivocally differentiated them from known T. nelsoni and T. britovi sequences. Based on the molecular data, six isolates were identified as T. nelsoni-like species, designated as T14 genotype; one isolate with a unique genotype, labelled as genotype T15; and three isolates exhibited mixed infections of T. britovi and the T14 genotype. This study suggests the presence of two novel Trichinella genotypes, T14 and T15, each with distinct genetic profile, emphasizing the role of leopards and tigers as sentinel hosts for Trichinella in India.